FACTORS AFFECTING ACADEMIC PERFORMANCE EFFECTIVENESS OF ACADEMIC STAFF AT PRIVATE UNIVERSITIES IN SHENYANG UNDER LIAONING PROVINCE - Mi, Cheng; Tipanark, Peerapong; Mungman, Pornthep (วารสารวิจัยธรรมศึกษา, 2024)
The objectives of this research were: (1) to determine factors affecting academic performance of academic staff at private universities in Shenyang under Liaoning Province, and (2) to propose a model of factors affecting academic performance effectiveness of academic staff at private universities in Shenyang under Liaoning Province. The total population of this study included 7,267 academic staffs from the private university in Shenyang. Proportional stratified random sampling method was used to collected data, totaling 400 academic staffs which calculated from package software. The main instrument for collecting data was a 5- level rating scale questionnaire. Descriptive statistics and inferential statistics such as SEM. Statistical were used to prove the hypotheses and used in path analysis. Overall, of data analysis through the statistical package software. Research results revealed that: 1) The effectiveness of academic performance of academic staff at private universities in Shenyang was moderate level. The factors affecting academic performance effectiveness were quality of work life, perceived organizational support, transformational leadership, job motivation, and job satisfaction, which had high level and 2) The factors affecting academic performance effectiveness of academic staff at the private universities in Shenyang with the statistically significant include quality of work life, perceived organizational support, transformational leadership, job motivation, and job satisfaction, all together could exactly direct/indirect predict the academic performance effectiveness was at 51 percent.